PROFILE OF SMOKING ADDICTION IN TEENAGERS IN INDIHIANG DISTRICT, TASIKMALAYA CITY - Ardiansyah Januar Pratama; Feida Noor Laila Isti'adah; Muhammad Muhajirin (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2024)
The purpose of this research is to determine the description of smoking addiction behavior among teenagers in the Indihiang District, Tasikmalaya City. Trends in smoking behavior between male and female teenagers among students in the Indihiang District, Tasikmalaya City. As well as the implications of Guidance and Counseling services to prevent smoking among teenagers in the Indihiang District, Tasikmalaya City. This research uses a quantitative descriptive approach to reveal the picture of smoking behavior in teenagers. The data collection technique used is incidental sampling, which is a technique for determining samples based on chance, meaning that anyone who meets the researcher by chance can be used as a sample. The data analysis technique uses data distribution calculations through average and standard deviation calculations, as well as percentage calculations and the SPSS 25.00 for Windows program to test the difference between two paired averages. In this study, the sample obtained was 147 teenagers. The results of this study show that the general picture of smoking addiction behavior among teenagers in Indihiang District can be concluded that overall teenagers in Indihiang District are in the very low category. This can mean that most teenagers have an addiction to cigarettes. However, it is necessary to increase positive activities so that there is no increase in smoking addiction. Based on the results of the profile of smoking addiction in adolescents in Indihiang District based on gender, the results were sig 0.0000.05, which means that significant differences were found between smoking addiction behavior in male and female adolescents, the implications for guidance and counseling service programs in the form of basic services. The basic service used is group guidance to reduce smoking habits in teenagers. This service uses group discussion techniques.